Evaluation of the Efficacy and Safety of Percutaneous Biopsy of Lung - McSweeney, Sean E (Bentham Open, 2012)
INTRODUCTION: Percutanous needle biopsy of the lung (PNBL), under image guidance, has established itself as a safe and effective minimally-invasive method of obtaining a tissue diagnosis of pulmonary lesions, for selected patients with suspected pathologic processes. The purpose of this study was to evaluate the diagnostic yield and safety of percutaneous core biopsy of the lung (PCBL) without Fine Needle Aspiration Biopsy (FNAB), with specific attention to potential risk factors that may predict post-biopsy pneumothorax. MATERIALS AND METHODS: A retrospective analysis of 75 consecutive PCBL procedures between January 2006 to March 2008 involving 72 patients with a documented pulmonary nodule or mass lesion on CT scan of Thorax. The study population included 38 males (52.8%) and 34 females (47.2%) aged 20-85 years (mean age 63.6 years). A co-axial cutting system with a 19-gauge outer needle and a 20-gauge inner automated cutting needle (Temno, Allegiance Healthcare Corporation, Ohio, USA) was used in all patients. RESULTS: Lesions varied in size from 0.7cm to 10.7cm (mean maximum trans-axial diameter 3.1cm). The mean number of core biopsy samples obtained was 3.1 (range 1-5). Of the 75 PCBL procedures, 71 yielded specimens adequate for histopathologic evaluation, consistent with a technical success rate of 95%. Malignancy was detected in 48 specimens (64%) and benign diagnoses were identified in 23 specimens (31%). As mentioned, 4 specimens (5%) were nondiagnostic. The most common biopsy-induced complication was pneumothorax, occurring in 15 patients (20%), with 4 (5.3%) requiring thoracostomy tube placement. CONCLUSION: PCBL without FNAB, under CT fluoroscopy guidance, has an excellent diagnostic accuracy in obtaining a conclusive histologic diagnosis of thoracic lesions and is comparable to FNAB in terms of safety and rates of occurence of complications.